Cardiovascular disease in rural Kuzbass aborigines - teleut - O. V. Ovsyannikova; V. M. Podkhomutnikov; A. V. Kolbasko; F. A. Luzina; E. V. Gus'kova (Российский кардиологический журнал, 2007)
The study is focused on cardiovascular disease and mortality dynamics in teleuts, living in a specific Western Siberia region (Kuzbass), situated in ecologically adverse intra-mountain basin with very high urbanization level. The rural teleut population represents one of so called small nations. The study (2005-2006) demonstrated arterial hypertension prevalence and 35-year mortality dynamics in teleut population.